Syuhudi Ismail's Thoughts About Hadith - Muhammad Jamil; Tajul Arifin (al-Afkar, Journal For Islamic Studies, 2025)
This research is motivated by the fact that the understanding of Hadith in Indonesia still faces various challenges, especially related to the application of the right methodology in the modern context. This research aims to analyze Muhammad Syuhudi Ismail's thinking in the methodology of understanding hadith, especially the textual-contextual approach he developed, as well as his contribution to the development of Hadith studies in Indonesia. This study applies a qualitative approach with historical-analytical methods, where data is obtained through literature study techniques on Syuhudi Ismail's main works. Then, the data was analyzed using qualitative data analysis techniques. The results of this study show that Syuhudi Ismail has succeeded in developing a comprehensive methodology for understanding Hadith by integrating textual and contextual aspects in a balanced manner. The findings of this study imply the need for a more holistic approach in the study of hadith in Indonesia, which not only prioritizes textual aspects, but also pays attention to the social, cultural, and historical context in the application of Hadith in contemporary society.